Volumetric Assessment of Maxillary Sinus and Pharyngeal Airway in Patients with Asthma and COPD: A CBCT Study - Aslıhan Artaş; Elif Meltem Aslan (Clinical Dentistry and Research, 2026)
Background and Aim: The goal of this research was tocomparatively evaluate the maxillary sinus and pharyngealairway volumes of patients with chronic obstructive pulmonarydisease (COPD) and asthma by employing cone-beam computedtomography (CBCT) scans.Materials and Methods: The study group comprised CBCTscans of 20 patients with COPD, 20 patients with asthma,and 40 healthy individuals. The volume of maxillary sinusesand pharyngeal airway in patients with asthma and COPDwere assessed by semi-automatic segmentation technique.ANOVA and the Kruskal–Wallis test were applied to analyze theparameters.Results: Pharyngeal airway volume was significantly higherin the control group (25561.1 ± 234.3 mm³) than in patientswith asthma (20250.5 ± 3871.6 mm³) and COPD (16894.7± 4223.9 mm³). In addition, pharyngeal airway volume wassignificantly higher in patients with asthma than in those withCOPD (p < 0.001). Maxillary sinus volumes were significantlylower in patients with COPD compared with healthy individuals(p = 0.001 for the right sinus and p < 0.001 for the left sinus),whereas no significant difference was observed between theasthma and control groups.Conclusions: These findings suggest that careful airwayassessment may be beneficial when planning generalanesthesia or procedures such as orthognathic surgery inpatients with asthma or COPD. In addition, reduced maxillarysinus volume in COPD may serve as a potential radiologicalmarker of chronic upper airway involvement.